2014
DOI: 10.3797/scipharm.1310-18
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Sesquiterpene Lactones from Kauna lasiophthalma Griseb

Abstract: Two new eudesmane derivatives (3 and 8) were isolated from the ethanol extract of the aerial parts of Kaunia lasiophthalma Griseb, together with 14 known eudesmane, germacrane, and guaiane sesquiterpenes, and four flavones. The structures and relative configurations of all the compounds were established by NMR spectroscopy and high-resolution mass spectrometry. The anticancer activity of sesquiterpenes 1, 3, 6–9, 11, 12, 14, and 16 was evaluated in vitro with the breast cancer cell lines HCC1937, JIMT-1, L56Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
(30 reference statements)
2
7
0
3
Order By: Relevance
“…However, further experiments are required to confirm any interactions between frullanolide and EGFR. Additionally and C 17 H 22 O 4 ranged between 9.3 and 27.0 µM (L56Br-C1 >SK-BR-3 >JIMT-1>HCC1937>MCF-7) and 3.2-11.0 µM (HCC1937>SK-BR-3>JIMT-1>L56Br-C1>MCF-7) (27). A previous computational structure-based screening method to identify natural compounds that specifically target the mouse double minute 2 homolog protein revealed that, out of the 35 top candidates, 8 eudesmanolide SLs (IJ-1, IJ-3, IJ-5, IJ-6, IJ-9, IJ-11, IH-45 and IH-49) exerted more potent anti-TNBC activity (MDA-MB-231) than anti-non-TNBC (MCF-7) activity at 72 h (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further experiments are required to confirm any interactions between frullanolide and EGFR. Additionally and C 17 H 22 O 4 ranged between 9.3 and 27.0 µM (L56Br-C1 >SK-BR-3 >JIMT-1>HCC1937>MCF-7) and 3.2-11.0 µM (HCC1937>SK-BR-3>JIMT-1>L56Br-C1>MCF-7) (27). A previous computational structure-based screening method to identify natural compounds that specifically target the mouse double minute 2 homolog protein revealed that, out of the 35 top candidates, 8 eudesmanolide SLs (IJ-1, IJ-3, IJ-5, IJ-6, IJ-9, IJ-11, IH-45 and IH-49) exerted more potent anti-TNBC activity (MDA-MB-231) than anti-non-TNBC (MCF-7) activity at 72 h (39).…”
Section: Discussionmentioning
confidence: 99%
“…Purified and crude compounds of one of these anticancer agents were reported to possess strong antitumor activity, with IC 50 values of ≤4 and ≤20 µg/ml, respectively (21). Several studies have identified specific SLs and derivatives which exhibit broad-spectrum antitumor activity towards several cancer types, including non-small cell lung cancer, colorectal cancer, leukemia, laryngeal cancer, gynecological cancer and breast cancer (13,(22)(23)(24)(25)(26)(27). The different anticancer abilities of SLs are associated with their carbocyclic skeleton classification (13,28 In the present study, frullanolide (a eudesmanolide) was assessed by MTT assay, and exhibited potent anti-breast cancer activity in breast cancer cell lines, including MCF-7, MDA-MB-468 and MDA-MB-231.…”
Section: Discussionmentioning
confidence: 99%
“…Four isolated compounds, zoapatanolide A, agathisflavone, anacardicin, and methyl gallate, were identified, and authors found that these components exhibited HeLa cell viability reduction in dose-dependent manner, although with distinct efficiencies: zoapatanolide A > anacardicin > agathisflavone > methyl gallate. The cytotoxic potential of zoapatanolide A is welldocumented in literature (212). This class of compounds act as Michael acceptor for the cysteines thiol groups, covalently modifying proteins (213,214).…”
Section: Anticancer Activitymentioning
confidence: 98%
“…Representative photomicrographs for the most potent compound identified as zoapatanolide A (1), a sesquiterpene α-methylene-γ-lactone, are shown(Figure 3), compared to and contrasted with those of agathisflavone(2), which is less than half as potent. The cytotoxic potential of sesquiterpene α-methylene-γ-lactones had been well reported in literature [35][36][37]. Concentration-dependent compound-induced reductions in HeLa cell viability (for compounds 1-3).…”
mentioning
confidence: 99%